Masjid al-Haram expansion: acceptance or criticism? - Omer, Spahic (IslamiCity, 2019)
As part of their latest expansion of al-Masjid al-Haram (the Holy Mosque), the Saudis are criticized for speedy and insensitive destruction of Muslim historical sites and architectural heritage, without taking into consideration the feelings and views of professionals, experts and even ordinary people.